Behaviour of self compacting concrete hybrid fiber reinforced hollow beams. (January 2022) - Anuradha, V.; Ch.Madhavi, T.
Abstract: This paper presents the investigations carried out to study the effect of longitudinal opening in a beam on its flexural strength and behaviour. Totally 10 full scale simply supported hollow hybrid fiber reinforced self compacting concrete beams of cross section 150 × 300 mm and span 3 m were tested under two point loading and their behaviour was compared with that of solid beam. Provision of openings lowers the moment of inertia leading to loss of strength. To overcome the loss of strength, hybrid fibers were used to strengthen the beam and improve ductility. Structural investigations were carried out to obtain the most optimum fiber content, the most optimum shape and most optimum location of opening. The experimental work included three groups of beams along with one control beam which was a solid beam without opening. The first group of 5 beams had hybrid fiber content in different proportions, the second group of 3 beams had longitudinal opening in different positions and the third group of 4 beams had different shapes of circular, square, triangular and rectangular openings. Beams were reinforced with 0.1% Nylon fibers and 0.1%, 0.2%, 0.3% and 0.4% micro steel fibers. The effect of position of opening is investigated by varying the position of 50 mm diameter circular opening and locating at 75 mm, 150 mm and 225 mm from the bottom fiber of the beam. Hybrid fibers containing 0.1% nylon fibers and 0.3% of micro steel fiber gave the best results in terms of workability, durability and strength. Results revealed that the first crack loads and ultimate loads decreased due to opening and the presence of opening in the tension zone had minimum loss of strength. Circular opening was found to be most optimum shape.